UNLOCKING THE INDUSTRIAL POTENTIAL OF MALOY BATUTA SEZ: A POLICY AND ECONOMIC PERSPECTIVE USING LQ AND SHIFT-SHARE ANALYSIS - Yusniar, Lely; Wicaksono, Agus Dwi; Prayitno, Gunawan (Directorate of Research and Community Service (DRPM), 2025)
The Maloy Batuta Trans Kalimantan (MBTK) Special Economic Zone (SEZ) in East Kutai Regency has significant potential for developing industries based on natural resources, particularly in palm oil and minerals. This study aims to assess the potential of leading sectors and evaluate the effectiveness of the MBTK SEZ development policy using a policy analysis approach, Location Quotient (LQ), and Shift Share analysis. The findings indicate that both national and regional policies have supported the growth of local resource-based industries; however, their implementation has not been optimal due to low investment levels and inadequate infrastructure. This study recommends aligning cross-sector policies, accelerating the provision of essential infrastructure, and implementing industrial clustering strategies to enhance the competitiveness of the MBTK SEZ.